A Novel Atraumatic Polymer-Assisted Peripheral Nerve Repair Device Compared With Microsurgical Neurorrhaphy - Diep Nguyen, PhD; Estelle Collin, PhD; Ricardo de Miguel, PhD, Dipl. ECVP; Edouard Reyes-Gomez, Dipl. ECVP, PhD; Ajul Shah, MD; Kyle R. Eberlin, MD (Journal of Hand Surgery Global Online)
Purpose: To evaluate the ability of a polymer-assisted device to repair transected peripheral nerve in comparison to microsuture neurorrhaphy. Methods: Twenty rat sciatic nerves were transected and repaired using either the polymer-assisted system or microsutures. Peripheral nerve functional recovery was evaluated through nerve conduction analysis performed at 1, 2, and 3 months. The gastrocnemius muscle mass ratio was measured. Peripheral nerve samples were imaged using microcomputed tomography. Local tissue response and nerve repair (including axonal density) were assessed through histology. Results: No significant differences in functional outcomes were observed between the polymer-assisted system and microsutures. Both groups showed signs of nerve conduction as early as 2 month, which increased by the 3 month end point where muscle regrowth reached 60% of the nonoperated contralateral leg. Microcomputed tomography and histological analysis revealed a trend of increased intraneural fibrosis and a significantly lower axonal density when microsutures were used for the repair (P < .05). Conclusions: The polymer-assisted system may reduce intraneural fibrosis compared to traditional microsutures, whereas functional recovery was found to be equivalent. Clinical relevance: The polymer-assisted nerve repair device provides an alternative to microsutures without inducing additional trauma to the damaged peripheral nerve ends because of the nonpenetrative nature of the device.